The association between vitamin D intake and sleep quality index within the 17-35 year age group - Veronika Maria Sidharta; Patricia Anggraeni; Komang Ardi Wahyuningsih; Mariani Mariani (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background : Vitamin D deficiency is a common health problem in the world, even in tropical countries such as Indonesia. The Lack of vitamin D intake from food or supplements can increase the risk of having vitamin D deficiency. The association between vitamin D and sleep quality has been proven by the discovery of vitamin D receptors in the brain and brainstem, which are the sleep centers of the body. Vitamin D also takes part in the process of light transduction and melatonin production, that affects circadian rhythm and sleep quality. Poor sleep quality often causes health problems which will affect the quality of life, work productivity, and increases the risk of death. The purpose of this study is to determine the association between vitamin D intake and sleep quality index within the 17-35 year age group.Method : This study is an observational analytic study using a cross-sectional approach. Data was collected using consecutive sampling methods. Vitamin D intake was measured by the Vitamin D Estimation Only - Food Frequency Questionnaire (VIDEO-FFQ) and sleep quality index was measured by the Pittsburgh Sleep Quality Index (PSQI). Data analysis is proceeded using the chi-square method.Results : The total of respondents were 119. 68,1% of the respondents had inadequate vitamin D intake and 80.4% of the respondents had poor sleep quality index. The analysis shows that there was no significant association between vitamin D intake and sleep quality index (p value = 0.325). Conclusion : Most of the respondents had inadequate vitamin intake and poor sleep quality index. There was no significant association between vitamin D intake and sleep quality index within the 17-35 year age group. Key words: Vitamin D intake, food and supplement, sleep quality index, 17-35 year age group